PELAKSANAAN DAN PENEGAKAN SANKSI KODE ETIK IKATAN NOTARIS INDONESIA DALAM PEMBAYARAN IURAN ANGGOTA DI KOTA YOGYAKARTA - , ANJAR KRISTIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to know about the implementation of the contribution and the establish of code of conduct sanction of Ikatan Notaris Indonesia in the case of notaryâs payment in the organization of Ikatan Notaris Indonesia in Yogyakarta. The type of research that used in this thesis is empiric juridical which is a research studying the work of law (the implementation of law) in the society. Juridical approach used to analyze the rules of legislation related with the implementation of code of conduct sanction to the violation of occupation by the notary. On the other hand, empirical approach used to analyze the law, which is seen as social behavior having a pattern in the society life that always correlated and connected in the social aspect. The result of this research is the collecting of the contribution did by the Executive Secretary, and this duty did well by coming into the concerned Notaryâs office or during the regular meeting. During the withdrawal of the contribution payment, there are some obstacles found. The obstacles are that there are members postponing the payment of the contribution, there are also members giving so many reasons to deny the payment, and also some members cannot be met in the office during the payment schedule. The obstacle emerges because the sanction given to the members is minor. This obstacle leads to another problem to the officers in taking the contributions. On the other hand, there are two opinion related to the strengthening of the sanction. First, people said that the strengthening of code of conduct sanction are done effectively, and there is awareness from the member to pay the contribution. Second, they said that the sanctions that are given is minor and it makes the members to ignore it. The Committee and Honorary Board are authorized only to warn orally to the members by means of satire or direct warning.